A case study of soil nematode populations under intensive cucumber monoculture in Hungary - Petrikovszki R.; Gódor A.; Nagy P. I.; Selmeczi D.; Simon B.; Tóth F. (Helminthologia)
A 25-year-old intensive monoculture of cucumber (Cucumis sativus ‘Monolit F1’) has been chosen for monitoring the effect of continuous fertilization, drip irrigation and various soil disinfection on free-living nematodes in soil. Densities, relative abundance of nematode genera, trophic groups and c-p classes, in addition, numerous nematological indices were determined besides certain soil properties. Concerning the nematological indices, all the values proved a stressed, depleted and unstable environment with degraded food web condition. The exaggerated application of fertilizers through irrigation caused high salinity values (0.62 %) which is much higher than the indicated toxicity threshold (0.4 %) for cultivated plants. The number of individuals of the bacterivore Acrobeloides and Cuticularia genera, which have a very high stress tolerance, was outstanding in the area. Besides juveniles, the appearance of Meloidogyne incognita males was also recorded which could lead to a change in the genetic composition of the population to adapt to environmental stressors. All these changes may result from salt stress indicated by intensive drip irrigation and the use of artificial fertilizers.